Advertising discourse as modelling and semiotic activity - Бойко, Ольга (Studia Philologica, 2024)
The article is aimed at analysing the basic concepts of semiotics and their application in multimodal advertising texts of consumer goods. The purpose of the article is to study advertising discourse as a modelling and semiotic activity in English-language advertising discourse, as well as to outline the main semiotic strategies and linguistic means in the formation of English-language advertising messages. The main objectives are to review the works of Ukrainian and foreign researchers on the issue, to identify and describe the key semiotic strategies and linguistic means of English-language advertising texts, and to determine the role of semiotic strategies in interaction with the audience and their reproduction of cultural concepts through advertising communication. The article provides a comprehensive overview of some of the key principles and concepts of semiotics and their advertising relevance, highlighting the construction of denotative messages about a product and desired connotative associations. The article also explains the role of adherence to known codes and the use of intertextual references in advertisements to create a connection with the audience. This article draws heavily on fundamental semiotic theories such as Peirce’s triadic sign model, the distinction between denotation and connotation, the role of codes and cultural conventions, and the phenomenon of intertextuality. The article shows how advertisers use signs, symbols and related meanings to create culturally resonating persuasive campaigns. The relevance of the study is to understand how advertising shapes attitudes and stereotypes, as well as how modern technologies change the ways of interacting with the audience through linguistic and semiotic strategies.